"Não pratique até acertar, pratique até não errar”: categorização analítico-semântica do aprendizado da técnica de punção guiada por ultrassom em modelo placentário de simulação. - Ana Clara Fidélis Rodrigues (2021)
Introduction: Learning the technique of invasive procedures is of fundamental importance in any area of human or animal health, as well as its categorization, in order to promote language standardization and performance control. The acquisition of technical skills requires intensive training not only until the first hit is reached, but until it is repeated consecutively. For this, the use of high-fidelity and validated biological models could obtain results close to the operative reality, aiming at quality control in a controlled environment. Ultrasound-guided puncture is a procedure requested in several medical specialties, however, many professionals still have difficulties in performing it with proficiency. Objective: To propose an analytical-semantic categorization of the learning of the ultrasound-guided cystic puncture technique in an ex vivo model of human placenta. Methods: The placentas used were irrigated with 0.9% saline solution to remove all remaining blood and intravascular clots. Each model consisted of two placentas and a finger of a latex glove filled with 5mL of saline solution was fixed between them to simulate the cyst. Twelve physicians performed ultrasound-guided puncture of the cystic lesion in the placental simulator. Subsequently, the performance of the participants was evaluated according to the number of attempts until they were able to correctly execute the three criteria of technique proficiency in a single time and then for three consecutive times. Statistical analysis of the data obtained was performed using the paired t-test to compare means, and the non-parametric test of signs (Wilcoxon test) to compare medians. Results: The average number of attempts to perform the three steps correctly for three consecutive times was 48.9 ± 6.7 attempts, 52.3% more than the average to be able to perform the three steps together for the first time (32 ,1 ± 6.1 attempts), with p<0.001. When performing the steps separately, viewing the needle throughout the procedure required a greater number of attempts (p<0.001). Among the other two tasks, the average number of attempts to visualize the complete emptying of the cyst was lower than the average number of attempts to identify the vessel early, with p=0.017 (p<0.05). Conclusion: The analytical-semantic categorization of ultrasound-guided cystic puncture learning can be divided into four phases called skill, competence, proficiency and mastery. The skill was obtained after a minimum of 8 punctures on average, with the execution of partial tasks correctly. The competence demanded a longer training, being reached after an average of 32 punctures, with the execution of all steps without errors for the first time. Proficiency, which is defined as the ability to perform all steps without error for 3 consecutive times, was achieved after an average of 49 punctures, about 50% more than what is needed to achieve initial competence. And mastery, which the study concluded to be humanly impossible, being attainable only by robotic surgery.